Proceedings of the Second International Conference on Mechatronics and Automatic Control - Wang, Wego (Springer, 2015)
This book examines mechatronics and automatic control systems. The book covers important emerging topics in signal processing, control theory, sensors, mechanic manufacturing systems and automation. The book presents papers from the second International Conference on Mechatronics and Automatic Control Systems held in Beijing, China on September 20-21, 2014. Examines how to improve productivity through the latest advanced technologies Covering new systems and techniques in the broad field of mechatronics and automatic control systems.